Electrical properties of 0.7Na0.5Bi0.5TiO3-0.2SrTiO3-0.1BaTiO3 lead free ceramic: An Off-Morphotropic phase boundary composition. (2022) - Praharaj, S.; Singha, A.; Rout, D.
Abstract: Probing in to the electrical behavior of ceramics is very essential for casting them in to real life applications. In this work, we report the temperature dependence of dielectric permittivity and impedance spectroscopic studies of 0.7Na0.5 Bi0.5 TiO3 -0.2SrTiO3 -0.1BaTiO3 to investigate its electrical properties. A Lorentz type law was found to well describe the diffused permittivity peak by two independent fitting processes. Such a peculiarity was related to the temperature response of the PNRs. This was ascertained from the temperature and frequency dependent Z* and M′′ spectra respectively. Combined graphs of normalized Z′′( f ) and M′′( f ) in the range 50 – 200 °C predict short ranged dipolar relaxations within the grains.